Diagnostic and Predictive Features of Pancreatic Cysts Using Endoscopic Ultrasound: A Retrospective Analysis from a Single Centre - Dumludağ, Ayşegül; Cindoruk, Mehmet (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Endoscopic ultrasound (EUS) has become an increasingly important tool in modern medicine, particularly in the diagnosis and treatment of pancreatic pathologies. The aim of this study is to elucidate the diagnostic and predictive roles of EUS in pancreatic cysts. Materials and Methods: Patients who underwent EUS for various clinical indications were retrospectively analyzed. Among them, the detailed characteristics of pancreatic cysts identified during the procedures were documented from the patients’ medical records. Results: A total of 1146 patients were included in the study, with a mean age of 56.4 years; 51.7% were female and 48.3% were male. Endoscopic ultrasound was primarily used to evaluate pancreatic lesions, focusing on cysts. Of a total of 200 pancreatic cysts evaluated pathologically, 74% (148) were benign, 24.5% (49) were malignant, and 1.5% (3) were borderline. No significant correlation was found between cyst size and malignancy (P = 1.00). However, malignancy rates significantly varied according to ultrasonographic characteristics, including simple cysts, mixed-type cysts (with solid components), pseudocysts, and infected cysts. The malignancy rate was significantly higher in mixed-type cysts (with solid components) (P = .0001). The presence of cyst-associated lymphadenopathy was also statistically significant for suspicion of malignancy (P = .005). Conclusion: This study highlights the importance of early diagnosis or surgical intervention for pancreatic cysts with mixed-type characteristics and associated lymph nodes. This underscores the need to prioritize triage for these patients. Cite this article as: Dumludağ A, Cindoruk M. Diagnostic and predictive features of pancreatic cysts using endoscopic ultrasound: A retrospective analysis from a single centre. Turk J Gastroenterol. 2025;36(12):852-857.